The Effectiveness of Women as Managers and its’ impact on Organizational performance: A Study on Educational Sector in Jaffna, Sri Lanka. - Yogendrarajah, R. (International Conference at Annamalai University, India – 2011, 2011)
The focus of the study is to explore the relationship between women‟s managerial effectiveness and organizational performance in Government Schools in Jaffna. Individual‟s managerial skills and characteristics of management are necessary to improve managerial effectiveness and achieve the organizational performance. This study was conducted to find out the general concept of the woman educator and her role as a school administrator in the society. The objective of the study was to identify the fit between the women managerial effectiveness and the organizational performance. The Central research question here is “To what extent managerial effectiveness of women managers‟/principals‟ lead to organizational performance?” To answer this question, data were gathered from Women principals, Vice principals, Deputy Principals and sectional heads in fifteen government primary and secondary schools. A total number of 65 questionnaires were sent out but a total of 43 responded. Simple statistical method of data analysis was used and it was discovered that female school mangers can perform with skills which leads to school performance. The study also showed that in terms of skills and characteristics in all areas reviewed, women able to attain effective management positions and can perform well to get good performance in the school. It was concluded that managerial effectiveness and organizational performance has positive relationship and the managerial effectiveness also one of the factor other than customer satisfaction, service quality, competitiveness which determine the organizational performance.
Keywords: Managerial effectiveness; Skills; Characteristics; Organizational performance